Towards a Rational Design of Zeolite-Polymer Composite Nanofibers for Efficient Adsorption of Creatinine. (22nd September 2016) - Takai, Ryo; Kurimoto, Rio; Nakagawa, Yasuhiro; Kotsuchibashi, Yohei; Namekawa, Koki; Ebara, Mitsuhiro
Abstract : This report describes the compositional and structural design strategy of a zeolite-polymer composite nanofiber mesh for the efficient removal of uremic toxins towards blood purification application. The nanofiber is fabricated by electrospinning composite solution of biocompatible poly(ethylene- co -vinyl alcohol) (EVOH) and zeolite particles which are capable of selectively adsorbing uremic toxins such as creatinine. By controlling electrospinning conditions carefully, the incorporated zeolites in EVOH were found to correspond closely to the feed ratios. Elemental mapping images of Si show that zeolites were uniformly blended within the fibers. The fabricated composite fibers successfully adsorbed creatinine from solution and the adsorption capacity reached a maximum at 12 h. The crystallinity of the nanofiber was also controlled by varying the composition of ethylene content in EVOH. Less crystallinity resulted in higher creatinine adsorption capacity due to the barrier property of EVOH. Cytotoxicity assay demonstrated that the composite fibers showed less toxicity than free zeolite particles which killed more than 95% of cells. The proposed composite fibers, therefore, have the potential to be utilized as a new approach to removing creatinine selectively from the bloodstream.